Exploratory application of a cannulation model in recently weaned pigs to monitor longitudinal changes in the enteric microbiome across varied porcine reproductive and respiratory syndrome virus (PRRSV) infection statuses - Opriessnig, Tanja; Halbur, Patrick; Bayne, Jenna; Rawal, Gaurav; Tong, Hao; Mou, Kathy; Li, Ganwu; Zhang, Danyang; Zhang, Jianqiang; Muwonge, Adrian (Frontiers in Veterinary Science, 2024)
Introduction: The enteric microbiome and its possible modulation to improve feed conversion or vaccine efficacy is gaining more attention in pigs. Weaning pigs from their dam on top of many routine procedures is stressful. A better understanding of the impact of this process on the microbiome may be important to improve pig production. The objective of this study was to develop a weaner pig cannulation model allowing ileum content collection from the same pig over time for 16S rRNA sequencing under different porcine reproductive and respiratory syndrome virus (PRRSV) infection status. Methods: Fifteen 3-week-old pigs underwent abdominal surgery and were fitted with an ileum cannula and ileum contents were collected over time. In this pilot study, treatment groups included a NEG-CONTROL group (no vaccination, no PRRSV challenge), a POS-CONTROL group (no vaccination, PRRSV challenge), a VAC-PRRSV group (vaccinated, PRRSV challenged), a VAC-PRO-PRRSV group (supplemented with probiotics, vaccinated, challenged with PRRSV) and a VAC-ANTI-PRRSV group (antibiotic administration, vaccinated, PRRSV challenged). We assessed the microbiome over time, measured anti-PRRSV serum antibodies, PRRSV load in serum and nasal samples, and severity of lung lesions. Results: Vaccination was protective against PRRSV challenge, irrespective of other treatments. All vaccinated pigs mounted an immune response to PRRSV within 1 week after vaccination. A discernible impact of treatment on the diversity, structure, and taxonomic abundance of enteric microbiome among the groups was not observed. Instead, significant influences on ileum microbiome were observed in relation to time and treatment. Discussion: The cannulation model described in this pilot study has the potential to be useful to study the impact of weaning, vaccination, disease challenge, and antimicrobial administration on the enteric microbiome and its impact on pig health and production. Remarkably, despite the cannulation procedures, all vaccinated pigs exhibited robust immune responses and remained protected against PRRSV challenge, as evidenced by development of anti-PRRSV serum antibodies and viral shedding data.